Infant and Toddler Examination Workshop for Preclerkship Medical Students - Miriam Schechter; Hai Jung Rhim; Mimi McEvoy (Association of American Medical Colleges, 2016)
Abstract Introduction Teaching the pediatric physical exam (PE) is commonly reserved for pediatric clerkships. However, with the trend toward aligning basic science curricula with clinical skills development, teaching the pediatric PE as a variation of the adult PE supports integrated learning. Methods This 2-hour infant and toddler examination workshop teaches the pediatric PE to 12-14 preclerkship medical students within a physical diagnosis course. Differences between the adult and the infant and toddler PE are made explicit, particularly regarding approach, sequence, and variations of the PE unique to infants and toddlers. Infants and toddlers are recruited from within the medical school community and serve as real subjects. Faculty examine one infant and one toddler in an interactive format, providing students the opportunity to learn the unique aspects of the pediatric PE and compare differences in growth and development. Results A retrospective pre-/postsurvey conducted after the workshop revealed that students' perception of their skill levels increased, specifically their approach to the pediatric PE, use of observation as an important examination modality, identification of unique pediatric PE components, performance of a developmental assessment, and interpretation of growth charts on all items. Discussion Our workshop's focus on teaching the pediatric PE to preclerkship students, ability to accommodate an entire class in a half-day session in a small-group interactive manner, and presence of actual infants and toddlers make it a distinctive contribution to the literature.